THE USED OF LEXICAL COHESION IN JAKARTA POST NEWSPAPER - Nur Habibah (Universitas Muhammadiyah Muara Bungo, 2021)
To make the reader understand what the writer means, the writer should compose a well form of the text. Cohesion plays the important role in creating the text. The purpose of this study are to find out what are the types of lexical cohesion in politic column as found in Jakarta Post newspaper and to find out what is the dominant of lexical cohesion in politic column as found in Jakarta post newspaper. This research is qualitative research with library research design the main data of this research is politic column as found in Jakarta Post. The result of this research showed that there are 5 types of lexical cohesion that found in politic column such as; 107 of repetition, 48 of synonym, 13 of antonym, 50 of hyponym and 30 of hypernym and the dominant of lexical cohesion that used in national column as found in the Jakarta Post newspaper is repetition.